Pelatihan Akuntansi Berbasis Aplikasi untuk Mahasiswa Manajemen dan Akuntansi di Jakarta - Machmed Tun Ganyang; Wier Ritonga (LPMP Imperium, 2021)
Community Service with the topic of Application-Based Accounting Training for high school students majoring in social studies was chosen because it saw the special needs of the social department. At the time of the industrial revolution 4.0, a disruptive era, especially during a pandemic where the majority of recording, reporting and other processes were carried out online or work from home, then the need for application-based accounting knowledge becomes very important. It is hoped that after participating in this training activity, partners will be proficient in using accounting applications such as MYOB and Zahir. Keywords: Accounting Application, IAI, SAK